Love interest : a novel - Gilmore, Clare (St. Martin's Griffin, 2023)
"Love Interest is Clare Gilmore's sparkling debut, a co-worker enemies-to-lovers rom-com that proves falling in love is the risk and the reward. Casey Maitland has always preferred the reliability of numbers, despite growing up the daughter of two artistic souls. Now a twenty-four-year-old finance expert working in Manhattan, Casey wonders if the project manager opening at her company - magazine powerhouse LC Publications - is a sign from the universe to pursue a career with a little more sparkle. That is, until she's passed over for the job in favor of the board chairman's son. Alex Harrison is handsome, Harvard-educated, and enigmatic. Everybody loves him - except for Casey. But when the two are thrown on the same project, they both have something to prove. For Casey, it's getting tapped for a transfer to the London office and fulfilling her dreams of travelling. For Alex, it's successfully launching a brand that will impress his distant father. As work meetings turn into after hours, Casey and Alex are drawn to each other again and again, but neither can avoid the messy secrets and corporate intrigue threatening to tear them apart. What they discover about their own company might change everything - including the dreams each of them is chasing"--